The Post-consumption Problem of Green Coconut in Brazil:: Alternatives and Sustainability (Sustainability in Debate, 2016)
This literature review explores the problem of post-consumption of green coconut in Brazil. It starts by offering an analysis of the general aspects of the coconut industry and its derivatives. It also highlights the origins of coconut by-products, as well as the impacts of the industry in rural and urban management. The properties and potential uses of coconut by-products are also evaluated. The review presents diverse theoretical approaches regarding the concept of sustainable development as applied to product design. Results reveal a wide range of potential applications of coconut by-products in the field of engineering, although there is still an evident lack of research into the management and logistics of the coconut production chain. We argue that the concept of sustainability must be interpreted broadly, but also objectively, in any future research in order to facilitate the sustainable consumption and post-consumption of the green coconut.